A New teaching method of improving capacity of visualisation and understanding of future mechanical engineers - Preda, Andrei (Technium Social Sciences Journal, 2020)
Being an aptitude, human intelligence needs to develop a lot of exercise and knowledge. The ability to understand, visualize and solve problems must be cultivated and rigorously guided. This paper presents a new integrated method of teaching the Technical Drawing and Infographics, with the purpose of training new students. The method is based on the observations of the teachers during the last years, their experience in education and the suggestions of the students. The results of applying this integrated method are quantifiable, leading to a better attendance at courses, towards 95%, at a much lower risk of school dropout and not least, creating bridges between abstract and reality.